Implication of Genetic Variants Near TCF7L2, SLC30A8, HHEX, CDKAL1, CDKN2A/B, IGF2BP2, and FTO in Type 2 Diabetes and Obesity in 6,719 Asians - Ng, Maggie C.Y.; Park, Kyong Soo; Oh, Bermseok; Tam, Claudia H.T.; Cho, Young Min; Shin, Hyoung Doo; Lam, Vincent K.L.; Ma, Ronald C.W.; So, Wing Yee; Cho, Yoon Shin; Kim, Hyung-Lae; Lee, Hong Kyu; et al. (Diabetes (New York, N.Y.), 2008)
Implication of Genetic Variants Near TCF7L2 , SLC30A8 , HHEX , CDKAL1 , CDKN2A/B , IGF2BP2 , and FTO in Type 2 Diabetes and Obesity in 6,719 Asians Maggie C.Y. Ng 1 , Kyong Soo Park 2 , Bermseok Oh 3 , Claudia H.T. Tam 1 , Young Min Cho 2 , Hyoung Doo Shin 4 , Vincent K.L. Lam 1 , Ronald C.W. Ma 1 , Wing Yee So 1 , Yoon Shin Cho 3 , Hyung-Lae Kim 3 , Hong Kyu Lee 2 , Juliana C.N. Chan 1 5 and Nam H. Cho 6 1 Department of Medicine and Therapeutics, The Chinese University of Hong Kong, Prince of Wales Hospital, Shatin, Hong Kong, China 2 Department of Internal Medicine, Seoul National University College of Medicine, Seoul, Korea 3 Center for Genome Science, National Institute of Health, Seoul, Korea 4 Laboratory of Genomic Diversity, Department of Life Science, Sogang University, Seoul, Korea 5 Li Ka Shing Institute of Health Sciences, The Chinese University of Hong Kong, Prince of Wales Hospital, Shatin, Hong Kong, China 6 Department of Preventive Medicine, Ajou University School of Medicine, Suwon, Korea Corresponding author: Maggie C.Y. Ng, maggiengatcuhk.edu.hk Abstract OBJECTIVE— Recent genome-wide association studies have identified six novel genes for type 2 diabetes and obesity and confirmed TCF7L2 as the major type 2 diabetes gene to date in Europeans. However, the implications of these genes in Asians are unclear. RESEARCH DESIGN AND METHODS— We studied 13 associated single nucleotide polymorphisms from these genes in 3,041 patients with type 2 diabetes and 3,678 control subjects of Asian ancestry from Hong Kong and Korea. RESULTS— We confirmed the associations of TCF7L2 , SLC30A8 , HHEX , CDKAL1 , CDKN2A / CDKN2B , IGF2BP2 , and FTO with risk for type 2 diabetes, with odds ratios ranging from 1.13 to 1.35 (1.3 × 10 −12 < P unadjusted < 0.016). In addition, the A allele of rs8050136 at FTO was associated with increased BMI in the control subjects ( P unadjusted = 0.008). However, we did not observe significant association of any genetic variants with surrogate measures of insulin secretion or insulin sensitivity indexes in a subset of 2,662 control subjects. Compared with subjects carrying zero, one, or two risk alleles, each additional risk allele was associated with 17% increased risk, and there was an up to 3.3-fold increased risk for type 2 diabetes in those carrying eight or more risk alleles. Despite most of the effect sizes being similar between Asians and Europeans in the meta-analyses, the ethnic differences in risk allele frequencies in most of these genes lead to variable attributable risks in these two populations. CONCLUSIONS— Our findings support the important but differential contribution of these genetic variants to type 2 diabetes and obesity in Asians compared with Europeans. Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 13 May 2008. M.C.Y.N., K.S.P., and B.O. contributed equally to this work. H.K.L., J.C.N.C., and N.H.C. contributed equally to this work. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted April 30, 2008. Received November 8, 2007. DIABETES